Comparison of the role of ultrasound guided transhepatic aspiration of gallbladder versus conservative management of acute calculous cholecystitis - Udupi, Vivek Ramesh; Neogi, Sushanto; Garg, Anju (International Surgery Journal, 2019)
Background: Gall stone disease remains one of the most common medical problem leading to surgical intervention. Cholecystitis accounts for 3-10% of abdominal pain worldwide. Acute cholecystitis is the most common complication of cholelithiasis accounting for 14 to 30% of cholecystectomies performed in many countries. Symptoms in cholecystitis are due to impaction of stone and subsequent distention of gallbladder with inflammation. Study is aimed to clarify the role of ultrasound guided transhepatic gallbladder aspiration in the early management of acute calculous cholecystitis. Methods: The study was conducted in total of 40 patients presenting with acute cholecystitis. 20 patients underwent ultrasound guided transhepatic aspiration of gallbladder with antibiotics (group A) and 20 patients were given antibiotics only (group B). Data were collected before intervention and post intervention duration of stay, pain according to visual analog scale, leucocytosis and fever were recorded for analysis. No complications were related to aspiration procedure. Results: Both groups were comparable. Group A patients had better pain relief (p=0.0001 day on 2 and p=0.004 on day 3 post aspiration), percentage reduction of leucocyte count (p=0.041 on day 3) and duration of hospital stay (p=0.004) which were statistically significant. Conclusions: Ultrasound guided transhepatic aspiration of gall bladder with antibiotics in acute cholecystitis results in better pain profile, faster reduction in leucocyte count and shorter duration of hospital stay when compared to antibiotics alone.